Relações entre durações e gesto corporal na performance de estudantes de harpa de concerto - Arícia Marques Ferigato (2020)
The present work proposed to investigate relationships between durations and body gesture in the performance of concert harp students seeking to understand how it achieves technical excellence and expressive control of performance in the concert harp. For such investigation, an experimental protocol was developed for an exploratory case study where the performances of 2 concert harp students from the harp bachelor's course were analyzed. From a collection of multimodal data of audio, video, motion capture and interviews, we sought to describe the relationship between changes in tempo and body gestures in the executions, as well as to verify a possible influence of metacognitive aspects of the participants in the evolution process of the consistency and coherence in the relationship between body gesture and musical content.